Got you fam or whatever people say....
We have equation 1 and 2
1. [tex]y= x^{2} +2x+3[/tex]
2. [tex]y=x+9[/tex]
Because equation 2 is simple and isn't quadtratic, we will insert 2 into 1,
[tex]x+9= x^{2} +2x+3[/tex]
[tex]0= x^{2} +x-6[/tex]
Then factor
x² +x -6=0
(x+3)(x-2)=0
x= -3, 2
Then using the values of x insert into either equation 1 or 2 to find y. I'm doing 2 because I'm lazy
y= x+9
when x=-3
y=x+9
= -3+9
= 6
(-3,6)
when x =2
y=x+9
= 2+9
= 11
(2,11)
Hence the co-ordinates are (2,11) and (-3,6)